STUDENTS’ SPEAKING SKILL THROUGH CONVERSATION PRACTICE A CASE OF GRADE EIGHT STUDENTS OF SMP MIFTAHUL HUDA - Shabilla Maurarin Rizqi; Hidayat, Nur; Nur Affini, Laily (LPPM STBA Pontianak, 2024)
Speaking is one of the English skills which students need to master. The researcher used the Qualitative method for this research to catch-all phrases that include participant observation and interviews. In this research, the author trying to find the level of students’ speaking ability, students’ problems in speaking English, and factors that influence students’ speaking ability. The author found that students’ speaking ability of grade 8 students of Miftahul Huda is still low, problems that relate to factors that influence students’ speaking ability, and two factors that influence students’ speaking ability internal and external. In this research, the authors conclude that 1. The students of 8 grade SMP Miftahul Huda have bad speaking ability; 2. Some problems and difficulties faced by students when practicing to speak English. It is felt embarrassed, nervous, inability to pronounce words correctly, fear, lack of motivation and confidence are a few challenges faced;3. The students’ speaking ability of SMP Miftahul Huda is influenced by 2 factors internal factor and external factor. Some of the internal factors are lack of motivation from themselves, lack of mastery of vocabulary, and afraid of mispronunciation. The second factor is external factors these are less supportive environments.